Contextualization of the19th century Islamic law in Buton (a study on Sultan Muhammad Idrus Qaimuddin thought about mawaris) - Muhammad Alifudin; Moh. Toriqul Chaer; Fitriah M. Suud (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2020)
This was a literary research about the contextualization of Islamic Law in Buton in the 19th Century. It proved a descriptive data about the paradigmatic basis used by Idrus Qaimuddin to re-actualize Islamic law in Buton. It utilized Von Eckartsberg’s phenomenological hermeneutic approach combined with Miles and Huberman’s analysis model. The study concluded that Idrus thought about mawaris was designed based on the Butonese needs and local character. It was product of Al-Qur’an constructed based on the spirit of reformation by prioritizing justice aspects to create social and cultural fairness. His attempt to re-interpret the mawaris verse showed his view on the text as something alive so that it needs a dialogue with condition and realities. Even though he did not explore much potentials of Islamic thurats which could enrich his views on mawaris, at least his thought proved that in the beginning of the 19th century, there was an Islamic scholar attempting to re-actualize Islamic teaching in this archipelago.